Analisis Literasi Digital Pustakawan Dalam Menghadapi Era Transformasi Masyarakat informasi - Nur Rizky, Muhammad Reza (Prodi Ilmu Perpustakaan dan Informasi Universitas Islam Negeri Raden Fatah Palembang, 2024)
This research uses scientific strategies to collect the data needed for research to investigate library digital literacy in the context of the millennial period. is a set of methods created by researchers that covers everything from data collection to analysis. The Mils Huberman model data analysis technique which is included in the qualitative research category is used by the author in this research as a type of library research. By using this method, researchers can obtain data by asking the author to look for relevant information in the manuscript. Research findings To keep up with the rapid advances in digital technology in the current Millennial Era, librarians' digital literacy skills must be strengthened. Modern era advances have connected all current activities with the internet for access to information. A new generation known as